Wolbachia infect ovaries in the course of their maturation: last minute passengers and priority travellers? - Lise-Marie Genty; Didier Bouchon; Maryline Raimond; Joanne Bertaux (PLoS ONE)
Wolbachia are widespread endosymbiotic bacteria of arthropods and nematodes. Studies on such models suggest that Wolbachia's remarkable aptitude to infect offspring may rely on a re-infection of ovaries from somatic tissues instead of direct cellular segregation between oogonia and oocytes. In the terrestrial isopod Armadillidium vulgare, Wolbachia are vertically transmitted to the host offspring, even though ovary cells are cyclically renewed. Using Fluorescence in situ hybridization (FISH), we showed that the proportion of infected oocytes increased in the course of ovary and oocyte maturation, starting with 31.5% of infected oocytes only. At the end of ovary maturation, this proportion reached 87.6% for the most mature oocytes, which is close to the known transmission rate to offspring. This enrichment can be explained by a secondary acquisition of the bacteria by oocytes (Wolbachia can be seen as last minute passengers) and/or by a preferential selection of oocytes infected with Wolbachia (as priority travellers).